A bleeding assessment tool correlates with intraoperative blood loss in children and adolescents undergoing major spinal surgery. Issue 152 (April 2017) - Anadio, Jennifer M.; Sturm, Peter F.; Forslund, Johan M.; Agarwal, Sunil; Lane, Adam; Tarango, Cristina; Palumbo, Joseph S.
Abstract: Screening laboratory studies for bleeding disorders are of little predictive value for operative bleeding risk in adults. Predicting perioperative bleeding in pediatric patients is particularly difficult as younger patients often have not had significant hemostatic challenges. This issue is distinctly important for high bleeding risk surgeries, such as major spinal procedures. The aim of this study was to determine if the score of a detailed bleeding questionnaire (BQ) correlated with surgical bleeding in pediatric patients undergoing major spinal surgery. A total of 220 consecutive pediatric patients (mean age 14.2 years) undergoing major spinal surgery were administered the BQ preoperatively, as well as having routine screening laboratory studies (i.e., PT, aPTT, PFA) drawn. A retrospective analysis was conducted to determine if there was a correlation between either the results of the BQ and/or laboratory studies with operative outcomes. A BQ score > 2 showed a strong positive correlation with intraoperative bleeding based on both univariate and multivariate analyses. In contrast, abnormalities in screening laboratory studies showed no significant correlation with operative bleeding outcomes. Relying on screening laboratory studies alone is inadequate. The BQ used here correlated with increased intraoperative hemorrhage, suggesting this tool may be useful for assessing pediatric surgical bleeding risk, and may also be useful in identifying a subset of patients with a very low bleeding risk that may not require laboratory screening. Highlights: This is the first analysis of a bleeding assessment tool in pediatric patients undergoing a high-risk major surgery. A strong correlation was observed between a high score on a bleeding assessment tool and intraoperative blood loss. Laboratory screening studies showed no correlation with intra- or post-operative blood loss. The potential utility of combining a bleeding assessment tool and more directed laboratory studies is discussed.